Nghiên cứu chế tạo compozit sinh học trên cơ sở nhựa polyeste không no gia cường bằng mat nứa lai tạo với mat thủy tinh. - Yến Oanh và cộng sự, Đoàn Thị (Vietnam Journal of Chemistry, 2014)
The preparation and mechanical properties of Neohouzeaua-glass fiber mat reinforced unsaratured polyester resin hybrid composite were investigated. The results showed that properties of the composite depend on the amount of Neohouzeaua fiber mat and the hybrid methods: skin-core and ply by ply hybridization. And the skin-core hybridization had better properties than ply by ply method. With reinforcing by 55% (by weight) of Neohouzeaua fiber mat, the tensile, flexural and impact strengths of received materials were 86.62 MPa, 99.12 MPa and 21.83 kJ/m2, respectively.  The water absorption of materials was studied and compared.